Bacterial Contamination and Antimicrobial Resistance in Two-Spotted (Gryllus bimaculatus) and House (Acheta domesticus) Cricket Rearing and Harvesting Processes - Jamlong Mitchaothai; Nils T. Grabowski; Rachakris Lertpatarakomol; Tassanee Trairatapiwan; Achara Lukkananukool (My University, 2024)
Food safety for cricket production is a crucial factor in producing edible crickets with safety for consumers and sustainability for two-spotted (
Keywords: Acheta; Gryllus bimaculatus; Insect Utilization and Effects